2013
DOI: 10.1002/biot.201300348
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic nanobead‐based bioassay provides sensitive detection of single‐ and biplex bacterial DNA using a portable AC susceptometer

Abstract: Bioassays relying on magnetic read-out using probe-tagged magnetic nanobeads are potential platforms for low-cost biodiagnostic devices for pathogen detection. For optimal assay performance it is crucial to apply an easy, efficient and robust bead-probe conjugation protocol. In this paper, sensitive (1.5 pM) singleplex detection of bacterial DNA sequences is demonstrated in a portable AC susceptometer by a magnetic nanobead-based bioassay principle; the volume-amplified magnetic nanobead detection assay (VAM-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Although measurements of the magnetic signal have continued to be of interest (Dieckhoff et al, 2014;Engström et al, 2013;Strömberg et al, 2014;Zardán Gómez de la Torre et al, 2011), optomagnetic readout strategies have attracted significant focus (Antunes et al, 2015;Bejhed et al, 2015;Donolato et al, 2015aDonolato et al, , 2015bMezger et al, 2015;Ranzoni et al, 2012;Tian et al, 2016;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although measurements of the magnetic signal have continued to be of interest (Dieckhoff et al, 2014;Engström et al, 2013;Strömberg et al, 2014;Zardán Gómez de la Torre et al, 2011), optomagnetic readout strategies have attracted significant focus (Antunes et al, 2015;Bejhed et al, 2015;Donolato et al, 2015aDonolato et al, , 2015bMezger et al, 2015;Ranzoni et al, 2012;Tian et al, 2016;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The assay strategies for the optomagnetic and magnetic readouts are essentially identical, but the two techniques probe very different properties of an MNP suspension and therefore they may respond differently when employed for readout in bioassays. For example, detection of the binding of MNPs to ~1 m large coils of DNA formed by rolling circle amplification has been performed by both techniques (Donolato et al, 2015a;Strömberg et al, 2014). There, the optomagnetic signal was observed to display a sign change when the circumference of MNP agglomerates approached the wavelength of the laser light and the scattering entered the Mie regime (Bejhed et al, 2015;Donolato et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Stromberg et al [65] demonstrated sensitive (1.5 pmol/L) singleplex detection of bacterial DNA sequence in a portable AC susceptometer by a magnetic nanobead-based bioassay principle. This was the first demonstration of biplex volume-amplified magnetic nanobead detection assay (VAM-NDA) in the susceptometer.…”
Section: Magnetic Nanoparticle Relaxation-based Sensorsmentioning
confidence: 99%
“…16 By utilizing a commercial AC susceptometer as read-out unit, we have demonstrated the versatility of this bioassay in several earlier studies. [17][18][19] We are currently focusing on developing a device, including automated sample preparation, for infectious diagnostics based on the bioassay principle using either a miniaturized AC susceptometer or a chip-based high-temperature superconducting quantum interference device. In connection to this work it is highly relevant to strive towards automation of the molecular protocol by investigating the possibilities for protocol simplifications.…”
Section: ′′mentioning
confidence: 99%